Impact of delivering iron-fortified salt through a school feeding program on child health, education and cognition: Evidence from a randomized controlled trial in rural India - Marion Krämer; Santosh Kumar; Sebastian Vollmer (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2018)
We present experimental evidence on the impact of delivering double-fortified salt (DFS), salt fortified with iron and iodine, through the Indian school-feeding program called "midday meal" on anemia, cognition and math and reading outcomes of primary school children. We conducted a field experiment that randomly provided one-year supply of DFS at a subsidized price to public primary schools in one of the poorest regions of India. The DFS treatment had significantly positive impacts on hemoglobin levels and reduced the prevalence of any form of anemia by 9.3 percentage points (or about 20 percent) but these health gains did not translate into statistically significant impacts on cognition and test scores. While exploring the heterogeneity in effects, we find that treatment had statistically significant gains in anemia and test scores among children with higher treatment compliance. We further estimate that the intervention was very cost effective and can potentially be scaled up rather easily.
Keywords: 330; Double-fortified salt; education; anemia; school feeding; India and randomized controlled trial